2021
DOI: 10.7759/cureus.15691
|View full text |Cite
|
Sign up to set email alerts
|

Liver Abnormalities in Systemic Lupus Erythematosus: A Prospective Observational Study

Abstract: In this study, we aimed to examine and analyze liver abnormalities among patients with systemic lupus erythematosus (SLE), including both newly diagnosed patients and those being followed up, as well as the prevalence of lupus hepatitis. MethodsThis was a prospective observational study. Clinical data, liver function tests (LFTs), and the findings from the ultrasonography of the abdomen among the patients were prospectively recorded and evaluated. ResultsOverall, 28 of the total 135 (20.7%) patients had liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 26 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…Therefore, patients with lupus nephritis ranked the high score of disease activity among the patients, subsequently increasing their expression of IRF5. Moreover, our result indicated that the IRF5 expression levels correlated positively with ALP in SLE (I) group, and this could be explained by Imran et al (2021) who found that overall, 28 of the total 135 (20.7%) patients had liver abnormalities, including liver function tests and those detected using ultrasonography. About nine patients had raised alkaline phosphatase (ALP) or gamma-glutamyl transferase (GGT) levels are higher two-fold than the upper limit of normal values [48].…”
Section: Correlation Between Expression Of Irf5 Gene and Other Parame...mentioning
confidence: 58%
See 1 more Smart Citation
“…Therefore, patients with lupus nephritis ranked the high score of disease activity among the patients, subsequently increasing their expression of IRF5. Moreover, our result indicated that the IRF5 expression levels correlated positively with ALP in SLE (I) group, and this could be explained by Imran et al (2021) who found that overall, 28 of the total 135 (20.7%) patients had liver abnormalities, including liver function tests and those detected using ultrasonography. About nine patients had raised alkaline phosphatase (ALP) or gamma-glutamyl transferase (GGT) levels are higher two-fold than the upper limit of normal values [48].…”
Section: Correlation Between Expression Of Irf5 Gene and Other Parame...mentioning
confidence: 58%
“…Moreover, our result indicated that the IRF5 expression levels correlated positively with ALP in SLE (I) group, and this could be explained by Imran et al (2021) who found that overall, 28 of the total 135 (20.7%) patients had liver abnormalities, including liver function tests and those detected using ultrasonography. About nine patients had raised alkaline phosphatase (ALP) or gamma-glutamyl transferase (GGT) levels are higher two-fold than the upper limit of normal values [48]. Takahashi et al (2013) concluded that dysfunction of the liver in the presence of SLE can be triggered by many factors, but when existing at the time of SLE onset, either SLE itself or drugs can be the reason.…”
Section: Correlation Between Expression Of Irf5 Gene and Other Parame...mentioning
confidence: 58%
“…Transaminitis is one of the common laboratory abnormalities seen in patients with newly diagnosed SLE, as seen in our patient. It is important to keep in mind that other causes of liver diseases such as medications, viral hepatitis, and alcohol are more common and need to be excluded before concluding the diagnosis of lupus hepatitis [15]. Anti-ribosomal P antibody was recognized to be associated with lupus hepatitis, but the clinical usefulness is limited.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Hepatocellular or cholestatic patterns in liver function tests indicate subclinical hepatic involvement in SLE. 3 SLE rarely presents with hepatic micro-abscesses. 4,5 SLE liver damage is commonly diagnosed one or more years after the initial diagnosis, indicating delayed hepatic involvement.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 SLE liver damage is commonly diagnosed one or more years after the initial diagnosis, indicating delayed hepatic involvement. 3 Up to 60% of SLE patients have liver function abnormalities, and 24% have hepatitis symptoms. [1][2][3] Many patients with lupus flares have elevated liver enzymes and hepatitis symptoms.…”
Section: Introductionmentioning
confidence: 99%